Targeted mutagenesis of a conserved anther‐expressed P450 gene confers male sterility in monocots. Issue 3 (14th October 2016) - Cigan, A. Mark; Singh, Manjit; Benn, Geoffrey; Feigenbutz, Lanie; Kumar, Manish; Cho, Myeong‐Je; Svitashev, Sergei; Young, Joshua
Summary: Targeted mutagenesis using programmable DNA endonucleases has broad applications for studying gene function in planta and developing approaches to improve crop yields. Recently, a genetic method that eliminates the need to emasculate the female inbred during hybrid seed production, referred to as Seed Production Technology, has been described. The foundation of this genetic system relied on classical methods to identify genes critical to anther and pollen development. One of these genes is a P450 gene which is expressed in the tapetum of anthers. Homozygous recessive mutants in this gene render maize and rice plants male sterile. While this P450 in maize corresponds to the male fertility gene Ms26, male fertility mutants have not been isolated in other monocots such as sorghum and wheat. In this report, a custom designed homing endonuclease, Ems26+, was used to generate in planta mutations in the rice, sorghum and wheat orthologs of maize Ms26 . Similar to maize, homozygous mutations in this P450 gene in rice and sorghum prevent pollen formation resulting in male sterile plants and fertility was restored in sorghum using a transformed copy of maize Ms26 . In contrast, allohexaploid wheat plants that carry similar homozygous nuclear mutations in only one, but not all three, of their single genomes were male fertile. Targeted mutagenesis and subsequent characterization of male fertility genes in sorghum and wheat is an important step for capturing heterosis and improving crop yields through hybrid seed.